2016
DOI: 10.1001/jamaophthalmol.2015.5479
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Function, Health Resource Use, and Total Health Care Costs Among Medicare Beneficiaries With Glaucoma

Abstract: IMPORTANCE The effect of glaucoma on nonglaucomatous medical conditions and resultant secondary health care costs is not well understood. OBJECTIVE To assess self-reported medical conditions, the use of medical services, and total health care costs among Medicare beneficiaries with glaucoma. DESIGN, SETTING, AND PARTICIPANTS Longitudinal observational study of 72 587 Medicare beneficiaries in the general community using the Medicare Current Beneficiary Survey (2004-2009). Coding to extract data started in Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
1
30
0
3
Order By: Relevance
“…Bringing a patient to the operating room for a glaucoma procedure (for glaucoma surgery or a physical agent for ciliary body destruction) is generally regarded as an important step by patients and their relatives 6. Moreover, it involves an additional cost to society due to the number of healthcare professionals involved in these procedures: nurses, anaesthesiologists and eye surgeons 7. The use of big data in ophthalmology has given rise to several reports on cataract, glaucoma and vitreoretinal surgical procedures 8.…”
Section: Introductionmentioning
confidence: 99%
“…Bringing a patient to the operating room for a glaucoma procedure (for glaucoma surgery or a physical agent for ciliary body destruction) is generally regarded as an important step by patients and their relatives 6. Moreover, it involves an additional cost to society due to the number of healthcare professionals involved in these procedures: nurses, anaesthesiologists and eye surgeons 7. The use of big data in ophthalmology has given rise to several reports on cataract, glaucoma and vitreoretinal surgical procedures 8.…”
Section: Introductionmentioning
confidence: 99%
“…common in glaucoma and has been linked to poor outcomes and increased healthcare costs. [1][2][3][4] Considering that glaucoma can lead to irreversible visual impairment and impact quality of life if not properly treated, [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and that the disease incidence rises as the world population ages, [19][20][21][22][23][24][25][26][27] efforts are being deployed to develop longer-term treatments that can alleviate nonadherence. Minimally invasive glaucoma surgery (MIGS) devices, for example, are being investigated because they can potentially lower intraocular pressure (IOP) over several years.…”
mentioning
confidence: 99%
“…A recent study of US Medicare beneficiaries revealed greater healthcare service use among individuals with glaucoma and greater morbidity in individuals with glaucoma with visual disability; the latter cohort was associated with a significantly greater likelihood of depression and mobility difficulty 33. Prior studies have corroborated the relationship between vision impairment and disability, with one identifying a relationship between glaucoma and greater rate of motor vehicle accidents 34–37…”
Section: Discussionmentioning
confidence: 99%